(untitled) (Research, Society and Development, 2022)
Introduction: Misoprostol is a prostaglandin E1 analogue with valence-restricted abortifacient properties, which is correlated with the presence of congenital abnormalities in newborns exposed in the uterus and, in Brazil, many women use inappropriate abortion methods. Objective: to establish a survey of data on Moebius syndrome in unsuccessful abortion attempts due to the use of misoprostol by low-income women. Methodology: For the preparation of this article, bibliographic research was carried out in search of articles available in the databases: Scientific Electronic, Scielo, Google Scholar, Brazilian Journal on Health Promotion, published between the years 2012 - 2021. Results and Discussions: The pharmacological action of Cytotec or Prostokos is direct on the prostaglandin receptors, acting on cervical collagen, causing changes in its physicochemical structure, and as a consequence, softening, erasing and maturation of the uterine cervix, in addition to promoting and stimulating uterine contraction. If the abortion attempt is not successful, it results in a disruptive vascular effect, causing damage to the nuclei and cells of the cranial nerves, occurring in the fourth week of pregnancy, impairing the development of limbs and organs, presenting a greater disposition to aggression and vulnerability to the manifestation of fetal malformations. Moébius Syndrome can manifest soon after birth, the child presents throughout the day a limitation when closing the eyelids and when sleeping cannot close them completely due to the abducens nerve paralysis. Conclusion: The need for greater investment in research on the proposed topic is affirmed.